What Is Acute Myeloid Leukemia? - Daniel Mazza Matos; Eduardo Magalhaes Rego (eJHaem)
ABSTRACT Background The recently published fifth edition of the World Health Organization (WHO) Classification and the International Consensus Classification (ICC) of myeloid neoplasms diverge in their definitions of acute myeloid leukemia (AML). Fundamentally, this current situation is problematic for two main reasons. First, the disagreement between the WHO and ICC reflects a conceptual conflict regarding the necessary and sufficient conditions for diagnosing AML. This leads to some confusion in areas such as nomenclature, therapeutic eligibility, clinical trial selection, and guidelines development. Second, in clinical practice, the two systems may assign different diagnoses to the same patient with a single disease entity. Such inconsistencies are unacceptable and highlight the urgent need for harmonization between the two classification systems. Topic In response, we put forward a proposal based on an unorthodox approach that combines philosophical reflections on essential and accidental properties with the latest clinical evidence concerning “AML subtypes with defining genetic abnormalities,” with the aim of initiating the unification of the WHO and ICC classification systems. Implications In this review, we propose a preliminary recommendation for a unified WHO‐ICC classification of five AML subtypes: AML with PML::RARA rearrangement, AML with NPM1 mutation, AML with KMT2A rearrangement, AML with MECOM rearrangement, and AML with in‐frame bZIP CEBPA. We hope that these initial efforts can be followed by a more definitive attempt to unify the WHO and ICC. Trial Registration The authors have confirmed clinical trial registration is not needed for this submission.